2020
DOI: 10.1002/pbc.28583
|View full text |Cite
|
Sign up to set email alerts
|

Childhood liver tumors in Argentina: Incidence trend and survival by treatment center. A report from the national pediatric cancer registry, ROHA network 2000‐2015

Abstract: Background: Information on the epidemiology of pediatric liver tumors in Latin America is limited. Purpose: To describe the incidence of liver tumors in a pediatric registry in Argentina according to geographic region, national trends over 16 years, and survival related to stage, age, sex, and care center. Methods: Newly diagnosed liver tumors cases are registered in the Argentine Pediatric Oncology Hospital Registry (ROHA) with an estimated coverage of 91% of national cases. Age-standardized incidence rate pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Peer‐reviewed published results from Argentina at a national level showed 61.7% 5‐year survival rate from 2000 to 2007, which improved to 72.2% in the period 2010–2014 as reported in a non‐peer‐reviewed official publication of the ROHA registry 14 . Brazil has no national registry but provincial registries cover large populations, reporting as in other large countries, survival discrepancies according to specific areas 28,34 . It is hoped that national registries now available in more Latin American countries will provide additional information to other countries to guide their national policies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peer‐reviewed published results from Argentina at a national level showed 61.7% 5‐year survival rate from 2000 to 2007, which improved to 72.2% in the period 2010–2014 as reported in a non‐peer‐reviewed official publication of the ROHA registry 14 . Brazil has no national registry but provincial registries cover large populations, reporting as in other large countries, survival discrepancies according to specific areas 28,34 . It is hoped that national registries now available in more Latin American countries will provide additional information to other countries to guide their national policies.…”
Section: Discussionmentioning
confidence: 99%
“…14 Brazil has no national registry but provincial registries cover large populations, reporting as in other large countries, survival discrepancies according to specific areas. 28,34 It is hoped that national registries now available in more Latin American countries will provide additional information to other countries to guide their national policies.…”
Section: National Cancer Registries For Childhood Cancersmentioning
confidence: 99%
“…In general, the recurrence rate of HB is 12% 23 . Uchida et al presented a five year overall survival of 80.9% of 100 patients with HB submitted to transplantation, which was the primary treatment in 69.4% of individuals 15 .…”
Section: Discussionmentioning
confidence: 99%
“…However, patients with metastatic disease still have a variable and poor outcome, with survival between 45-80% 3 . Moreno et al, in a 15 year survey of the pediatric population in Argentina, reported a five year survival rate of 74.7% and 35.3% for HB patients with localized and metastatic disease, respectively 23 . The survival observed in this study was compatible with the literature, being 91.7% overall and 81.5%, disease-free.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other malignant conditions in children and adolescents, liver tumors are relatively rare. A previous retrospective analysis suggested that the incidence rate was 1.8/million per year (1). Hepatoblastoma (HB), hepatocellular carcinoma (HCC), and embryonal sarcoma (ES) are the top three most frequent liver tumors in children and adolescents (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%